Dynamic and static corrosion of alpha-alumina bonded refractory in contact with molten soda-lime-silica (SLS) glass. Issue 1 (January 2019) - Wang, Zihua; Maotsela, Tlamelo; Toperesu, Phillip M.; Kale, Girish M.; Daji, Jafar; Parkinson, David
Abstract: The corrosion behaviour of sintered high purity α-Al2 O3 refractory composition in contact with soda-lime-silicate (SLS) glass has been investigated using a dynamic corrosion test designed to simulate industrial conditions. Experiments were conducted as function of rotation speed, contact time duration and temperature. The results of dynamic corrosion tests are in excellent agreement with those obtained from static crucible test at 1370 °C for 72 h which is a standard industrial testing practice. The phase composition and microstructures of the glass-refractory interface of these samples were studied by X-ray Diffraction (XRD) and combined Scanning Electron Microscopy – Energy Dispersive X-ray Spectroscopy (SEM-EDS), respectively. Elemental mapping was also carried out on the glass-refractory interface.